Sustainable agriculture and food sovereignty in Haiti: sharing knowledge and shaping understanding of food systems at the University of Fondwa - Joseph, Lesly; Stephenson, Max O.; Zanotti, Laura; Ricot, Scutt (Frontiers in Sustainable Food Systems, 2023)
The Association of Peasants of Fondwa (APF), a grassroots organization led by a visionary Haitian Spiritan priest, established the private nonprofit University of Fondwa (UNIF) in Haiti in 2004. The University aims to fill a gap in educational opportunities for rural youth and to develop community leaders able to steward food security, sustainable farm animal husbandry, and small business development. Since the institution’s foundation, University faculty members have explored low-input sustainable agriculture techniques, which were inspired by strategies shared earlier by Cuban agronomists and adapted to the Fondwa region’s mountainous terrain. While the University has faced and continues to confront many challenges related to its sustainability as an institution, this article describes the processes by which its faculty and students have conducted diagnoses of soils and crop choices, the innovations they have developed and introduced to improve harvest productivity in rural Haiti and, especially, the ways and means by which they have sought to share such (re)thinking of traditional practices with local farmers. We argue that the University of Fondwa faculty’s close collaboration with local farmers and the agricultural techniques they have refined thereby have not only improved food security for the families involved but have also contributed to the creation of social capital in the countryside and enabled participating Haitian farmers to imagine a path toward food sovereignty. In addition, by educating farmers and providing them tools to improve their food production, the University has worked to close the deep inequality gap that exists between urban and rural Haiti.